The American party battle : election campaign pamphlets, 1828-1876. - Silbey, Joel H. (John Harvard library., 1999)
The 19th century was the heyday of furious contention between American political parties, and Joel Silbey attempts to capture the drama and substance of those battles in a representative sampling of party pamphlets.